Prevalence of gingivitis and risk factors among pregnant women from Acapulco, Guerrero: a cross-sectional study - Gallardo Chávez, Lisa Madison (2022)
Introduction: Gingivitis is a condition that has been associated with an exaggerated inflammatory response of the gums to oral biofilm, attributed to the secretion of hormones during pregnancy. Objectives: To estimate the prevalence of gingivitis and identify associated risk factors among pregnant women in a medical clinic from Acapulco, Guerrero. Material and methods: Cross-sectional study in a convenience sample of 92 pregnant women, during the period from January to March 2020. A self-administered questionnaire collected sociodemographic data, economic income, oral hygiene habits and personal pathological history. The periodontium was evaluated based on the new classification of gingival health and gingivitis induced by oral biofilm on six representative teeth. Multivariate analysis identified factors associated with gingivitis using the odds ratio and its 95% confidence interval as an estimate of the strength of association with CIETmap statistical software. Results: The prevalence of gingivitis was 60% (55/92). Two factors remained in the final model of the multivariate analysis. The main associated strength was found in the variable of not using oral hygiene aids (ORa= 6.76; 95%CI= 2.01-22.78). The other variable was not attending dental visits (ORa= 3.74; 95%CI= 1.44-9.73). Conclusion: The prevalence of gingivitis reported was similar to other studies. With the factors found, it is suggested to reinforce preventive measures to reduce the presence of gingivitis in pregnant women.